The Boston Stone at Creek Square, ca. 1910 - Unknown (Tufts Archival Research Center, 2005)
View of The Boston Stone, which is embedded in the southeast elevation of 116 Blackstone Street, located on Creek Square. A sign for the Marshall House Restaurant is visible to the left of The Boston Stone. Originally used for grinding paint; became unofficial marker from which to measure distance, ca. 1737. Image is part of the Henry P. Curtis Collection. 5 7/8 x 8 Photographs